A Discourse on Completely Regular Space - Samuel Amoh Gyampoh; Frank Kwarteng Nkrumah (Archives of Current Research International, 2019)
This study is an investigation of some of the relationships which exist between various generalizations of completely regular spaces. The primary aim of the study is to look at the separation axioms and delve more into one of the claims about completely regular space; “Every completely regular space is a regular space as well”.